Estratégias regulatórias baseadas em comércio de emissão de poluição: os casos da política de qualidade do ar do Estado de São Paulo e do RenovaBio - Amorim, Aline Zaed de (2022)
This research aims to analyze the use of emissions trading schemes as regulatory instruments in the context of air pollution control policies. Therefore, we intend to carry out a case study based on two public policies in Brazil that set up air pollution emission trading mechanisms, as environmental regulatory instruments, to meet pollution emissions reduction targets. The first policy is an initiative developed under the scope of São Paulo’s Air Quality Policy – outlined in São Paulo State Decree nº 59.113/2013 - in which pollution compensation is possible through the use of emission credit reduction. The second policy is a decarbonization credits market (CBIO) established in the National Biofuels Policy (RenovaBio), by Law No. 13.576/2017, whose context is part of the agenda for combating climate change. The objective is to analyse the regulatory design of these public policies, focusing on the regulatory strategy based on the creation of emission trading, aiming to answer: (i) whether the regulatory tools for this approach, necessary to enable an emission trading, were effectively implemented; (ii) the extent to which they were used by the regulated parties of these instruments; and (iii) what the main difficulties faced in the implementation of these regulatory instruments based on pollution emission trading systems were.